Side Effects of CV Medications Following Hospitalization for ACS Are Associated With More Frequent Health-Care Contacts. (May 2017) - Le, Rachel J.; Cullen, Michael W.; Lahr, Brian D.; Wright, R. Scott; Kopecky, Stephen L.
Background: Patients hospitalized for first acute coronary syndrome (ACS) are frequently discharged on multiple new medications. The short-term tolerability of these medications is unknown. Methods: This single-center cohort study assessed 30-day health-care utilization and how it may be impacted by medication prescribing trends. We included Olmsted County patients presenting with ACS and previously undiagnosed coronary artery disease in 2008 to 2009. All health-care contacts were reviewed 30 days after index hospital discharge for potential adverse medication effects including documented hypotension or bradycardia, or symptoms likely attributed to the medications. Results: The study included 86 patients; their mean age was 63 (standard deviation: 15.5 years). Antianginal or antihypertensive cardiovascular (CV) medications were prescribed to 98% of patients at discharge; 76% were prescribed 2 or more. There were 233 health-care contacts in 30 days; 90 (39%) of these contacts were unscheduled. More CV medications tended to be prescribed to patients with unscheduled contacts, both pre-ACS ( P = .045) and upon hospital discharge ( P = .051). Hypotension and/or bradycardia at follow-up occurred in 52 patients (60%). Surprisingly, there was no association between hypotension and/or bradycardia at follow-up and increased health-care utilization ( P = .12). Potential adverse drug effects were reported in 34 (40%) patients. These patients had significantly more total health-care contacts ( P < .001) and unscheduled health-care contacts (median 0 vs 1.5; P < .001). Conclusions: Symptoms of adverse drug effects were associated with more frequent health-care utilization after ACS. Clinicians need to consider this while striving to increase patient compliance with post-ACS medications and optimize care transitions.